Antipseudomonal activity enhancement of luminescent iridium(iii) dipyridylamine complexes under visible blue light12. Issue 12 (22nd November 2017) - Sauvageot, E.; Elie, M.; Gaillard, S.; Daniellou, R.; Fechter, P.; Schalk, I. J.; Gasser, V.; Renaud, J.-L.; Mislin, G. L. A.
Abstract : The antibacterial activity against P. aeruginosa of the biotin or glycoside derivative of iridium(iii )-dipyridylamine complexes is potentiated by blue light. Abstract : Cyclometallated iridium(iii ) dipyridylamine complexes present antibacterial activity against P. aeruginosa, a highly resistant pathogenic bacterium. This activity is increased when the complex is conjugated to biotin, a bacterial nutrient, and a MIC of 4 μM (4 μg mL −1 ) has been observed. The irradiation of P. aeruginosa cultures with blue LED light potentiates the anti-bacterial activities of these iridium(iii ) complexes when they are conjugated to a glycoside.